The impact of an unequal distribution of education on inequalities in life expectancy - Clemens Danler; Katharina Pfaff (Elsevier, 2021)
Prior research has found socio-economic determinants such as education to affect health outcomes. Yet, education is not distributed equally among the population. This article attempts to quantify the impact of unequal distribution of education on inequalities in life expectancy. We calculate a Gini coefficient of longevity from the life tables provided by the Human Mortality Database and a Gini coefficient of education using data on educational attainment from Barro and Lee (2013). We estimate linear regression models to examine the relationship between inequality in education and inequality in life expectancy at the country level for up to 31 European countries between 1970 and 2010. Results provide empirical evidence for a statistically significant positive association between educational inequality and inequalities of longevity. Confounding factors reflecting individual health behaviour such as cigarette or alcohol consumption do not exert a separate statistically significant effect on inequality in life expectancy. Findings are robust to alternative calculation of key variables, dropping a potential outlier, and an alternative estimation approach. These findings suggest that not only education, but also equality in education is a crucial factor for health outcomes. Continuing efforts should be directed towards the reduction of educational inequality in order to reduce inequality in longevity within a country.